2016
DOI: 10.4012/dmj.2015-429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple firings on the microstructure of zirconia and veneering ceramics

Abstract: The aim of study was to evaluate the effects of multiple firings on the microstructures of zirconia and two ceramics. Vita VM9 (VM-Z) and Cerabien ZR (C-Z) ceramics on a zirconia framework and zirconia without veneering ceramic (WO-Z) were evaluated. Firing methods included firing two, five, and ten times (n=10). The effects of multiple firings on the surface hardness of the materials were evaluated using a Vickers hardness (HV) tester. Data were analyzed by two-way ANOVA and Tukey's test (α=0.05). After firin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It is important to remember that during manufacturing restorations that are consisted of a zirconia substructure covered with a feldspathic ceramic using the layering technique, explored herein, its usual to execute many firing cycles during the application of the 1st dentin layer, 2nd dentin layer, enamel, and/or even finally with the glaze material to achieve the final thickness of restauration [9]. So, our data corroborate that such processing would inherently lead to alterations of color, optical characteristics, and also potentially impact the mechanical properties of the future restoration, in accordance with prior studies [9,22,23,24]. In fact, a previous study [22] reported that veneering ceramics fired 10 times showed higher density and less porosity than those fired twice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to remember that during manufacturing restorations that are consisted of a zirconia substructure covered with a feldspathic ceramic using the layering technique, explored herein, its usual to execute many firing cycles during the application of the 1st dentin layer, 2nd dentin layer, enamel, and/or even finally with the glaze material to achieve the final thickness of restauration [9]. So, our data corroborate that such processing would inherently lead to alterations of color, optical characteristics, and also potentially impact the mechanical properties of the future restoration, in accordance with prior studies [9,22,23,24]. In fact, a previous study [22] reported that veneering ceramics fired 10 times showed higher density and less porosity than those fired twice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is fundamental that veneering ceramics (such as feldspathic) have good mechanical properties through appropriate confection and firing processes. It is already known that the multiple firing cycles of the veneering feldspathic ceramic applied over zirconia cores can effectively improve its hardness [8,9]. Also, according to Hasssija et al [10], repeating firings did not affect the color parameters of ceramics with metal core.…”
Section: Introductionmentioning
confidence: 92%
“…Nonetheless, other studies evaluating monolithic porcelain specimens, observed that increasing number of firings can improve hardness, density, and decrease porosity. 45,46 Among the included studies, only one evaluated the effect of glaze firing on bilayer specimens. 25 The experimental groups included one that was just polished and another polished and self-glazed, which presented higher flexural strength.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies indicated that multiple firings have effects on the microhardness and flexural strength of zirconia; 10 mechanical properties and microstructure of veneering ceramics; 2 and the bond strength between veneering ceramic and zirconia framework. 11,12 Also, different firing procedures were reported to cause alterations in microstructural properties and surface characteristics of zirconia 9,13 and were associated with clinical performance and longevity of zirconia restorations. 14 Another factor considered to influence the clinical performance of zirconia restorations is the bond strength between luting material and restoration.…”
Section: Introductionmentioning
confidence: 99%
“…In simple clinical procedures, zirconia restorations usually undergo 2 to 5 firings after sintering for veneering procedure. 9 However, multiple firings may be required to correct the occlusion, marginal adaptation, contours or color of the veneering porcelain. 2 Previous studies indicated that multiple firings have effects on the microhardness and flexural strength of zirconia; 10 mechanical properties and microstructure of veneering ceramics; 2 and the bond strength between veneering ceramic and zirconia framework.…”
Section: Introductionmentioning
confidence: 99%